Sistem Tempat Sampah Pintar dengan Notifikasi dan Visualisasi Tingkat Kepenuhan Sampah Berbasis Internet of Things - Akmal Ahmadi Muslih; Desi Rahmawati Lubis; Devia Dwi Anggi; Nurlaila Fatra; Nirwan Sinuhaji; Abdullah (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
Lifting from the problem of garbage scattered around the trash can area, this problem can now be handled with a study on smart trash bins. The method used is design where the test is carried out on the proximity sensor, the height of the garbage and the data response to the Telegram application. This trash can uses Arduino Atmega328 technology and the internet of things (IoT). The system will be made of a supporting circuit, namely, the HC-SR04 sensor as object detector and garbage data. In the next section there is also an output in the form of an LED as an immediate notification of the state when the trash is full or empty. If the garbage reaches LED 1 then the trash is at level 1 and vice versa if the trash can is full then LED 5 will light up which means the trash can is full.